Translocation and dissemination of commensal bacteria in post-stroke infection - Stanley, Dragana; Mason, Linda J; Mackin, Kate E; Srikhanta, Yogitha N; Lyras, Dena; Prakash, Monica D; Nurgali, Kulmira; Venegas, Andres; Hill, Michael D; Moore, Robert J; Wong, Connie H Y (Nature medicine, 2016)
In humans and rodent models, commensal gut bacteria contribute to post-stroke infection. Experimental stroke in rodents causes gut barrier dysfunction and permeability, enabling translocation and dissemination of host gut microbiota. Bacterial infection is highly prevalent in patients who have had a stroke. Despite the potential contribution of micro-aspiration in post-stroke pneumonia, we found that the majority of the microorganisms detected in the patients who developed infections after having a stroke were common commensal bacteria that normally reside in the intestinal tracts. In a mouse model of ischemic stroke, post-stroke infection was only observed in mice that were born and raised in specific-pathogen-free facilities; this was not seen in mice that were born and raised in germ-free facilities. Using high-throughput 16S rRNA gene amplicon sequencing and bioinformatics analyses, we provide evidence demonstrating that the source of the bacteria forming the microbial community in the lungs of post-stroke mice was indeed the host small intestine. Additionally, stroke-induced gut barrier permeability and dysfunction preceded the dissemination of orally inoculated bacteria to peripheral tissues. This study identifies a novel pathway in which stroke promotes the translocation and dissemination of selective strains of bacteria that originated from the host gut microbiota.